Consécration de la faune et de la flore comme motifs esthétiques et d’identité culturelle dans l’art mexicain du xxe siècle - Christine Frérot (Caravelle)
In the 19th century Spanish-American volcanoes were a subject of study chosen as representative of Spanish-American nature and landscape. The scientific discoveries inspired European and New World artists who focused on vernacular flora to exalt new values, not only esthetic, but identity and nationalist ones as well. The Mexican pictorial production, specially since the 1910 Revolution, includes inescapable botanical references such as the cactus or the watermelon, sometimes related with the local fauna. Concerning the flower, it has gradually turned into a feminist symbol in Mexican contemporary art.